PENGARUH EKSISTENSI TRANSPORTASI UMUM BUS RAPID TRANSIT MAMMINASATA TERHADAP DAYA TARIK ANGKOT DI KOTA MAKASSAR - Rusdi, Rusdi; Wulandari, Andi Triwenni; Ibrahim, Ibrahim (Universitas Negeri Makassar, 2023)
This research was conducted to find out: 1) Description of the existence of the mamminasata bus rapid transit public transportation, 2) Description of the attractiveness of public transportation in the city of Makassar, 3) how does the existence of the mamminasata rapid transit bus affect the attractiveness of public transportation in the city of Makassar. The research method used in this study is a descriptive quantitative approach method. The research variables consist of the existence of the mamminasata rapit transit bus(Variable X) and the attractiveness of public transportation (Variable Y). The techniques used for data collection are observation, questionnaires or questionnaires as well as documentation. The data analysis technique used is descriptive statistics and inferential analysis. Based on the research results, it is known that: 1) The description of the existence of the Mamminasata rapid transit bus (variable X) in the